Reconfiguring power in Portuguese higher education - Magalhães, António; Veiga, Amelia; Videira, Pedro (Education Policy Analysis Archives, 2018)
This paper aims to analyse the shift in the internal power balance between managerial and academic self-governance as reflected in the perceptions of teaching and non-teaching staff on the tendencies, decision-making processes and actor’s roles in these processes. The empirical data used in this paper were gathered on the basis of an on-line survey, distributed throughout 2014 and 2015 in all Portuguese higher education institutions. Responses were interpreted taking into account the influence of governance narratives on the development of boardism, i.e., a decrease of academic self-governance reflecting the decline of the power of teaching staff in HEIs’ governance; an increase of managerial governance as reflected in the reinforcement of hierarchies and organisational top-down decision-making; and the influence of external stakeholders. The analysis contributes to dig into the complexity of the governance arrangements challenging the prevailing influence of the NPM governance narrative while underlining the internal dynamics of HEIs, where Portuguese teaching staff continue to play a key role.